2004
DOI: 10.1158/0008-5472.can-04-1129
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic Acid Increases the Expression of p53 and Proapoptotic Caspases and Sensitizes Keratinocytes to Apoptosis

Abstract: Retinoids influence growth and differentiation of keratinocytes (KCs) and are widely used for the management of skin diseases and for prevention of nonmelanoma skin cancer (NMSC) in predisposed patients. Here we investigated the effect of all-trans-retinoic acid (ATRA) on KC apoptosis. When KCs were cultured in confluent monolayers for several days, they acquired resistance against UVB-induced apoptosis. In contrast, when the cells were treated with 1 mol/L ATRA for 6 days and subsequently irradiated with diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(76 citation statements)
references
References 49 publications
2
71
0
3
Order By: Relevance
“…In keratinocytes, RA treatment was reported to upregulate the expression of several caspases. The mechanism by which RA increases caspase expression in these cells remains unknown, but it has been shown that although their overexpression does not induce apoptosis by itself, it sensitizes the cells to apoptosis induced by UVB irradiation and by doxorubicin (36). We show here that in MCF-7 cells, RA increases the expression of several proapoptotic genes and leads to pronounced apoptosis without the need for additional agents.…”
Section: Discussionmentioning
confidence: 62%
“…In keratinocytes, RA treatment was reported to upregulate the expression of several caspases. The mechanism by which RA increases caspase expression in these cells remains unknown, but it has been shown that although their overexpression does not induce apoptosis by itself, it sensitizes the cells to apoptosis induced by UVB irradiation and by doxorubicin (36). We show here that in MCF-7 cells, RA increases the expression of several proapoptotic genes and leads to pronounced apoptosis without the need for additional agents.…”
Section: Discussionmentioning
confidence: 62%
“…Indeed, RA/IFN combination was previously shown to exert synergistic antiproliferative and proapoptotic effects in different cancer cell systems (11,12). With particular regard to the proapoptotic activity, these compounds can variably promote both the downregulation of antiapoptotic proteins such as Bcl-2, Bcl-xL, and Mcl-1 (12,13), often overexpressed in B-NHLs, including MCL (14)(15)(16)(17)(18) and/or the induction of proapoptotic proteins, including Bax, Noxa, and XAF1 (12,(19)(20)(21)(22)(23).…”
Section: Mantle Cell Lymphoma (Mcl) Is a Distinct Cd5mentioning
confidence: 99%
“…[1][2][3][4]. These effects are critical for maintaining skin health and suppressing carcinogenesis in skin (1,2,(4)(5)(6). Despite extensive knowledge of various retinoid-dependent gene expression effects in epidermal and other cell types, however, much less is known about retinoid transport events at the cell membrane; and endocytosis of circulatory vitamin A carrier proteins by epidermal cells or epidermoid cancer cells remains poorly understood and controversial (see below).…”
Section: Introductionmentioning
confidence: 99%